CONTROL OF POWDERY MILDEW OF PEA BY GINGER EXTRACT - P. SINGH and G. D. MISHRA, U. P. SINGH, B. P. SRNASTAVA (Indian Phytopathology, 2002)
Ginger (Zingiber officinale) rhizome extract, fresh and stored, at two different temperatures, viz,S and 15Â°C for one month was used at three different concentrations (10000, 15000, 20000 pprn) to control powdery mildew of pea (Pisum satiuum) under field conditions during 1986-87 and 1987-88. The highest dose of the fresh extract gave the best result as compared to the stored ones. Statistical analysis of the data obtained in the field indicated that the results are mostly significant.